Study of the Dependence of Biological Dry Matter Accumulation on Seed Sowing Dates and Rates in Winter Triticale Varieties - R.Sh.Tellayev; U.D.Bobatova (American Journal of Botany and Bioengineering, 2026)
This article provides information on the nutritional value of triticale, uses and species of triticale, history of origin and distribution, and results of the studied of the dependence of biological dry matter accumulation on seed sowing dates and rates in winter triticale varieties in the condition of the republic of Uzbekistan.